The relationship between supervisory board and management and their communication processes in publicly listed companies in Poland - Jacek Gad (Comparative Economic Research. Central and Eastern Europe, 2015)
The focal point of this study is to present the results of empirical research concerning operation of supervisory boards in the practice of companies listed on the Warsaw Stock Exchange (WSE). The main subject of interest concerns two research areas: the character of the relationship between as well as the methods and tools employed in communications between a supervisory board and management. The research paper consists of theoretical concepts regarding the supervisory boards' tasks and the relationship between a supervisory board and a management board. Moreover, another area of interests concerns legislative changes that, according to the author, have had a great influence on functioning of supervisory boards in the practice of WSE-listed companies. The conclusions presented in the paper have been formulated on the basis of a review of the literature, analysis of pertinent regulations, and a questionnaire survey of members of supervisory boards which was conducted in September, October and November 2011 (the data was obtained by means of postal surveys).
Keywords: 330; supervisory board; management; corporate governance; communication